Rapid determination of single base mismatch mutations in DNA hybrids by direct electric field control - Sosnowski, Ronald G. (The National Academy of Sciences of the USA, 1997)
We have demonstrated that controlled electric fields can be used to regulate transport, concentration, hybridization, and denaturation of single- and double-stranded oligonucleotides. Discrimination among oligonucleotide hybrids with widely varying binding strengths may be attained by simple adjustment of the electric field strength. When this approach is used, electric field denaturation control allows single base pair mismatch discrimination to be carried out rapidly (<15 sec) and with high resolution. Electric field denaturation takes place at temperatures well below the melting point of the hybrids, and it may constitute a novel mechanism of DNA denaturation.